Abdominopelvic hydatid disease during pregnancy: a systematic review of the literature - Evangelos Chinis; Kyriakos Tzanakis; George Lockett; Laura Burney Ellis; Stergios Bobotis; Georgios Geropoulos; Maria Kyrgiou; Konstantinos S. Kechagias (Frontiers in Global Women's Health, 2026)
Objective To review the available literature on abdominopelvic cystic echinococcosis (CE) during pregnancy, focusing on clinical presentation, diagnostic approaches, management strategies, and maternal and foetal outcomes. Methods A systematic review was conducted in accordance with PRISMA guidelines. Studies reporting abdominopelvic hydatid disease in pregnant women were included without restrictions on study design or geography. Results Fifty-one studies (45 case reports and 6 case series) including 79 patients were analysed. The mean maternal age was 28 years (range 15–42). Most patients with reported clinical-presentation data were symptomatic (56/67, 83.6%), commonly presenting with right upper quadrant or nonspecific abdominal pain. Ultrasound was the primary diagnostic modality (50/52, 96.1%), while MRI was used in selected cases. The liver was the most frequently involved site (50/72, 69.4%), followed by pelvic and adnexal locations. Surgical intervention was performed in 38.5% of cases, conservative management in 30.8%, and cyst aspiration in 14.1%. Surgery was often timed during caesarean section or the second trimester. Benzimidazole therapy was administered to 31 patients, most commonly during pregnancy. Caesarean delivery occurred in 43.3% and vaginal delivery in 34.3% of cases. Adverse pregnancy outcomes included miscarriage (4.5%), termination of pregnancy (3.0%), one maternal death (1.5%), and one neonatal death (1.5%). Among the 36 pregnancies with reported gestational age at delivery, 13 (36.1%) resulted in preterm birth. Conclusion Abdominopelvic CE during pregnancy is rare and clinically challenging, with substantial heterogeneity in presentation and management across the published literature. Given the limited available evidence, management should be individualised within a multidisciplinary team, while prospective international registries are needed to strengthen the evidence base.